Analisis Pengetahuan tentang Perbankan Syariah Santri Pondok Pesantren Al-Ittihad Mojokerto dan Pengaruhnya terhadap Minat Menabung di Bank Syariah - Tita Octavina Fauzy; Agus Purwadi; Rahmad Hakim (Iqtishodia: Jurnal Ekonomi Syariah, 2019)
This study aims to determine the correlation between the knowledge owned by students of Al-Ittihad Mojokerto Islamic boarding school to the interest in saving in Islamic banking. This study is a quantitative and the data collection method used questionnaires. The results of this study, the significance value of the variable students’ knowledge was equal to .000 < .05 and there was a positive influence between the variable of knowledge of students about Islamic banking (X) towards the interest in saving in Islamic banking (Y). Therefore, Ho is rejected and Ha is accepted. Moreover, the result of r_ (count) is .753 greater than r_ (table), which is equal to .195. According to the criteria, the relationship between the dependent and independent variables showed a strong and significant correlation between the variable knowledge of students and interest in saving. Moreover, the knowledge was greater so, the interest of saving also was greater. It was expected for further research, in order to increase the number of respondents and variables. The results of further research can be further elaborated.